The Influence of Organizational Culture, Work Environment, and Organizational Commitment on Employee Job Satisfaction at De Tonga Hotel Medan - Teguh Setia Jaya Waruwu; Daud Arifin; Soulthan Saladin Batubara (Cattleya Darmaya Fortuna, 2026)
This research aimed to analyze the influence of organizational culture, work environment, and organizational commitment on employee job satisfaction at De Tonga Hotel Medan. The population in this study consisted of 61 employees of De Tonga Hotel Medan, with a sample size of 61 respondents. The sampling technique used was saturated sampling. This research utilized primary quantitative data collected through questionnaires and processed using SPSS Version 25. The research was conducted in 2026. The data analysis technique employed a multiple linear regression model. The results of the research showed that organizational culture partially had a positive and significant effect on employee job satisfaction at De Tonga Hotel Medan, with a regression coefficient of 0.388, a t-value of 3.220, and a significance value of 0.008. The work environment partially had a positive and significant effect on employee job satisfaction, with a regression coefficient of 0.691, a t-value of 6.039, and a significance value of 0.000. Organizational commitment partially had a positive and significant effect on employee job satisfaction, with a regression coefficient of 0.596, a t-value of 5.513, and a significance value of 0.036. Simultaneously, organizational culture, work environment, and organizational commitment had a positive and significant effect on employee job satisfaction, with a significance value of 0.000 and an F-value of 337.750. The most dominant variable influencing employee job satisfaction was the work environment, with the largest Standardized Coefficients Beta value of 0.634. Additionally, 94.3% of employee job satisfaction could be explained by organizational culture, work environment, and organizational commitment, while the remaining 5.7% was influenced by other factors outside the research model. Employee job satisfaction had a very strong correlation with organizational culture, work environment, and organizational commitment, as indicated by an R-value of 0.978.